Pseudoargumentacja i jej wpływ na aksjologię tekstu (analiza wybranych mikrotekstów polsko i rosyjskojęzycznego dyskursu publicznego) - Król-Kumor, Martyna (Studia Rossica Posnaniensia, 2025)
Evaluative judgments implying evaluation, appearing in the course of the public narrative, are usually accompanied by various types of pseudo-argumentation. The aim of the analysis is to typologize the arguments found, to determine which of the methods of pseudo-argumentation issued most often and whether it is possible to find significant analogies or differences in the use of this narrative device in the Polish and Russian public discursive space. The pseudo-arguments identified in the analyzed texts of the articles were divided into six groups: arguments relating to emotions, intuition, obviousness, tradition, authority and crowd. The most numerous group were references to authorities, including the so-called “experts” and “analysts”. It is also worth noting that the least representative group of pseudo-arguments were references to tradition, which may be symptomatic of other changes in the contemporary information society. An important issue is also the subject matter of axiologically marked microtexts. In Polish-language value judgments, criticism of Russia was most often implied, while Russian public discourse was axiologically dominated by the denial of the West as a provocateur of the armed conflict in Ukraine. The isolation of pseudo-arguments from public discourse text sand their typologization in the comparative context of two different ethnic discourses is the result of combining discourse analysis and textual linguistics with axio-linguistic methods and elements of rhetoric. This made it possible to conduct a study, the results of which may be interesting from the point of view of differences in the ways of verbalizing evaluation in different linguistic spaces.